Characteristics of Cutaneous and Subcutaneous Infectious Granuloma at a Signal Center in China: A Five-Year Retrospective Study - Zhen-Zhen Yan; You-Ming Mei; Hai-Qing Jiang; Yong-Nian Shen; Pan-Gen Cui; Wei-Da Liu; Mei-Hua Fu; Hong-Sheng Wang; Jian-Fang Sun (Wolters Kluwer Health, 2019)
Abstract. Objective:. Cutaneous and subcutaneous infectious granuloma (CSIG) is a broad group of inflammatory conditions that share important similarities in granulomatous reaction pattern and nonspecific clinical presentation. Here, we conducted the retrospective study to identify the clinical, pathological, and epidemiological correlations of CSIG cases at a signal center in China. Methods:. Data of patients diagnosed with CSIG between January 1, 2011 and December 31, 2015 were retrospectively collected, including socio-demographic information, pathogen diagnosis, clinical features, pathological results, treatment, and prognosis. Results:. This study included 256 patients (137 males and 119 females) with a mean age of 52 years. Infections were more common in those aged over 40 years old (76.17%). The most common pathogens were Mycobacterium leprae (26.56%), Sporothrix schenckii (23.83%), and Mycobacterium tuberculosis (15.63%). Mycobacterium marinum (8.98%) accounted for 51.11% of nontuberculous mycobacterial contagion. Lesions were most common in the distal extremities (32.03%). The predominant clinical forms were plaques (61/142, 42.96%) and nodules (41/142, 28.87%). Conclusions:. Various pathogens were responsible for the CSIG cases in this study, with M. leprae being the most common. CSIG should be considered as a likely diagnosis for patients with lesions on exposed parts of the body that present as plaques or nodules and has a history of trauma.